Indonesia's new capital: can Jokowi find the money? - Borsuk, Richard (2022)
President Joko Widodo has pushed ahead to launch his most ambitious project – building a new capital from scratch in remote Kalimantan, Borneo. Can Indonesia find the estimated US$32.5 billion needed for building a smart and green city in the jungle?